(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2019)
Most of the software applications are configured as client-server fashion in the network in order to enable communication among them. But sometimes these applications must be able to communicate or exchange data between clients and server that are not always up and active. One of the solutions to such issues is to enable applications to store information and communicate asynchronously with other. Thus in this regard Message Oriented Middleware (MOM) which support massage queue based communications are becoming more and more popular today. It is the task of developer to choose the suitable broker for his applications. Thus one has to compare different MOM based brokers to select suitable and efficient ones. This paper mainly compares two brokers RabbitMQ and RESTful API. By conducting survey on different experimental results it can be concluded, that when large number of users are involved in network communication, RabbitMQ is more stable and suitable to use.